Enhanced DNA binding of 9-omega-amino alkyl ether analogs from the plant alkaloid berberine - Islam, Md Maidul; Basu, Anirban; Hossain, Maidul; Sureshkumar, Gopalsamy; Hotha, Srinivas; Kumar, Gopinatha Suresh (DNA and Cell Biology, 2011)
To understand the structure-activity relationship of isoquinoline alkaloids, absorption, fluorescence, circular dichroism, and thermodynamics were employed to study the interaction of five C-9-omega-amino alkyl ether analogs from the plant alkaloid berberine with double-stranded calf thymus DNA. The C-9 derivatization resulted in dramatic enhancements in the fluorescence emission of these compounds. The most remarkable changes in the spectral and binding properties were in the BC4 and BC5 derivatives. Interactions of these analogs, which have an additional recognition motif with DNA, were evaluated through different spectroscopic and calorimetric titration experiments. The analogs remarkably enhanced the DNA binding affinity and the same was directly dependent on the alkyl chain length. The analog with six alkyl chains enhanced the DNA binding affinity by about 33 times compared with berberine. The binding became more entropically driven with increasing chain length. These results may be of potential use in the design of berberine derivatives and understanding of the structure-activity relationship for improved therapeutic applications.